Does The Size of a Public Accounting Firm Effects the Relationship Between Financial Distress, Fee Audit, Audit Delay and Auditor Switching? - Solihin, Atang; Purwasih, Desy (Universitas Pamulang, 2023)
This study aims to analyze and provide empirical evidence of the effect of financial distress, audit fees, and audit delay on auditor switching with KAP size as a moderating variable. The type of research used is a quantitative approach with associative methods. The population in this study are property and real estate sector companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The sampling technique in this study was purposive sampling. The data analysis technique used is logistic regression using E-Views version 12 software. Based on the analysis results, it is known that financial distress, audit fees, and audit delay simultaneously affect auditor switching. Partially, economic pain and audit delay do not affect auditor switching, while audit fees affect auditor switching. The logistic regression analysis (MRA) results show that KAP size cannot moderate financial distress, audit fees, and audit delay on auditor switching.